PSYCHOLOGICAL EFFECTS OF BREASTFEEDING FOR MOTHERS-CHILD AND ITS RELATIONSHIP WITH ISLAM: A SYSTEMATIC REVIEW - Amanah, Nuraini Khoirotun; Karimah, Fadhilah Nurul; Fedro, Alfarid (Universitas Islam Negeri Alauddin Makassar, 2021)
Psychological Effects of Breastfeeding for Mothers-Child and Its Relationship with Islam: A Systematic Review. At least mothers recommend that all babies worldwide be exclusively breastfed for 6 to 24 months. However, very limited studies have examined the psychological effects of mother-child specifically for exclusive breastfeeding and related to the duration of breastfeeding in Islam up to 24 months. This article aims to review the literature on the relationship between the psychological effects of mother-child breastfeeding and Islam from the PubMed database in the last six years using the PRISMA method. As a result, four papers from five studies were found to be eligible for review. Such maternal-child psychological effects have been reported to be highly predictive such as anxiety, postpartum depression, neurological and emotional development, and maternal self-efficacy for breastfeeding, attitudes towards breastfeeding towards the duration of exclusive breastfeeding up to 24 months. It is related to the Islamic teaching that breastfeeding is associated with the belief system and Islamic values, which play an essential role in improving health education, moral and spiritual, and psycho-spiritual (physical, mental, intellectual, and heart. Research to date shows that the mother-child psychosocial effect is not only influenced by the duration of exclusive breastfeeding up to 24 months but can also be changed through the intervention and the experience of both. However, there are very limited studies that specifically examine the psychological effects of exclusive breastfeeding duration of up to 24 months. Interpreting the results of the available literature is difficult due to the various methodologies and definitions of breastfeeding duration and the small sample size. Further studies, in particular, longitudinal cohort studies are needed that examine the determinants of the psychological effects of breastfeeding duration and infant feeding methods from pregnancy to 24 months postpartum. Keywords: Psychological effects, mother-child, Islam, breastfeeding.